Exploration of the presale property market in China from an institutional perspective - Leung, Barbara Y. P.; Ma, Athenda S. C. (International Journal of Strategic Property Management, 2013)
Presales have been used as a major financing mode for real estate development in China. However, there have been limited researches studying the roles of different real estate market players impacting on the efficiency of the property presales, in particular, on the issue of asymmetric information in the market. The paper adopted an institutional approach to study the problems latent in the presale property market. Semi-structured interviews with professionals and industry practitioners were conducted and the findings suggested that the lack of market information, pseudo policy objectives and confusing roles played by major market players are the root of the problems. Restructuring of the institutional arrangement in regard to the financial channels for capital, risk management on developers, custody of the presale proceeds and commitment of the regulatory authorities are necessary in enhancing the market efficiency.First Publish Online: 23 Sep 2013